Peran Full Cost Recovery dalam Penentuan Tarif Desa Wisata: Studi Kasus pada BUMDes - Susanto, Heri; Rosita, Rosita; Hidayat, Riskin; Kade R.K., Ida Ayu (Jurnal Bisnis dan Kewirausahaan, 2024)
This study aims to analyze the tariff determination in Village Owned Enterprises (BUMDes) based on Full Cost Recovery (FCR) methods and its impact on the rural community. The research was conducted in Tourism Village, Daerah Istimewa Yogyakarta, representing the implementation of BUMDes tariff policies. This study will explore the factors influencing tariff setting and examine the economic and social implications at the local community level in the context of a tourism-oriented village enterprise. By utilizing a Full Cost Recovery approach, the research encompasses both direct and indirect costs associated with the services provided by the Village Owned Enterprises. The various factors that impact tariff setting, including operational costs, community expectations, and market demand. Additionally, it will evaluate the broader economic and social effects of these tariffs on the local population, assessing whether they enhance or hinder community well-being. By focusing on a tourism-centric village, this research seeks to provide a nuanced understanding of how Full Cost Recovery principles can be effectively applied in rural settings. The findings are expected to contribute valuable insights into the tariff-setting processes within similar communities and inform policymakers on strategies to balance economic sustainability with social equity.